(untitled) (Fiep Bulletin - online, 2011)
External causes of mortality, according to the international classification of diseases, correspond to a large portion of deaths in most countries, getting always between the second and third cause of death in total deaths. Stand out among the external causes murders, traffic accidents, drowning, crashes and burns. In Brazil the external causes of death in occupies the second position in the rating of the leading causes of death. This study aimed to identify the main types of external causes of deaths in the State of Alagoas-Brazil in the period from 2000 to 2008, with emphasis on drowning. The data were obtained in Legal State Medical Institute, and processed in the program SPSS 16.0. Data of IBGE were used for the calculations of mortality rates. In the period of study, 20,624 deaths from external causes, distributed in 11,193 homicides, 5,337 traffic accidents, 2,733 deaths caused by various causes and 1,360 by drowning. The murder as external cause of death, has been increasing steadily over the period, while drowning suffers minor fluctuations, with mortality rates ranging from 4.41 and 6.03 by 100,000 gender male/s (73%) presents the greatest frequency of mortality by drowning, the latter taking place mainly in natural waters. In the last decades, Brazil has gone through a lot of changes in the epidemiological profile of grievances health, both in relation to infectious diseases as non-infectious. This caused the deaths by external causes became one of the leading causes of death among the population. Being the drowning the third cause of death in the State of Alagoas, it is necessary that this fatality is best studied to implement specific policies of prevention.